L’impact du contexte discursif sur l’usage de la métaphore dans le discours journalistique - Abir Amel Mouhadjer; Boumediene Benmoussat (Multilinguales)
The written press in Algeria represents a discourse rich in strategies which serve to transmit information ; These are guided by social conditions. In this article we have attempted to study the discursive environment of a single strategy, which is the metaphor. By trying to elucidate the influence of society on the use of the metaphor but also the influence of the use of the metaphor in certain social conditions.